Adopting Lean Supply Chain at Unipharma Syria to Improve its Response to Clients - Aram H Massoudi (International Journal of Supply Chain Management, 2019)
Abstract This research aims to test the impact of the adoption of lean supply chain standards in improving Unipharma Syria response to its clients' posts the Syrian crisis of 2011. The researcher used descriptive and analytical approach to study Universal Pharmaceutical Industries. UNIPHARMA one of the well-known highly developed firms in the Pharmaceutical Industries in Syria. The data was collected from a questionnaire distributed to 100 employees working at Unipharma Damascus, 98 valid responses were received. The hypotheses were tested using SPSS software. The result of the research showed that the company's reliance on process standardization and industrial standards was relatively high and the adoption rate for industrial standards are the highest. The company's response rate to its customers in terms of flexibility and delivery is not high and convergent for both variables. Keywords lean supply chain, customer response, Process Standardization, Industrial Standards